Numerical analysis of multi-functional antenna array composed of differently sized elements - Gangwar V.S.; Kumari Modi J.; Sreenivasulu K.; Singh A.K.; Singh S.P. (My University, 2025)
In this study, an innovative approach for the synthesis of multi-functional antenna (MFA) array is proposed. The multi-functionality is achieved through the distribution of antenna elements operating at different frequencies which share the same physical aperture. A new variant of genetic algorithm designated as modified binary coded GA (MBC-GA) is investigated to find out best possible combinations for inter-element spacings between elements of same frequency and elements of different frequency corresponding to desirable radiation patterns. To estimate the functioning of proposed approach for the synthesis of multi-functional antenna array, two randomly spaced planar antenna (RSPA) arrays consisting of 4×4-element array operating at 1.5 GHz and 8×8-element array operating at 3.3 GHz have been interleaved into common aperture and examined numerically. © 2018 IEEE.